Духless 21 века. Селфи: [роман] / Сергей Минаев - Минаев Сергей Сергеевич (АСТ, 2015)
Экземпляры: Атабаевская с/б (20230302) / Инвентарный номер: 47260 / Цена: / Авт.знак: М 61 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44